Perception and liking of soups flavored with chipotle chili and ginger extracts: Effects of PROP taster status, personality traits and emotions. (April 2019) - Scott, Nicole O.; Burgess, Brenda; Tepper, Beverly J.
Highlights: PROP status influenced liking of chili-tomato soup but not ginger-squash soup. Sensation seeking influenced liking of chili-tomato soup but not ginger-squash soup. Only the chili flavoring influenced emotional ratings of the soups. Disgust was a negative predictor of overall liking for both soups. Except for disgust, different factors predicted liking of the two soups. Abstract: Individual differences in perception and liking of spicy foods are well known, but poorly understood. Most studies have investigated this phenomenon using chili pepper (capsaicin), while neglecting other pungent spices. This study examined the role of PROP taster status (a genetic marker for oral sensations), personality factors, and emotions in perception and liking of tomato and butternut squash soups flavored with chipotle chili and ginger extracts, respectively. Each extract was added at three concentrations: low, medium and high. Overall, the chili extract had a greater influence on the sensory profile and emotional ratings of the tomato soup than the ginger extract on the squash soup. Specifically, PROP non-tasters liked the burn of the tomato soup at the high chili extract concentration more than the other taster groups, high sensation seekers liked the burn from the low and high chili extract concentrations more than low sensation seekers, and emotional ratings for 'disgust', 'mouthwatering', and 'relaxed' were altered after soup tastings. Predictors of overall liking also differed between the soups; burn intensity, 'disgust' and the PROP x 'disgust' interaction predicted liking of the chili tomato soup, whereas ginger flavor, overall flavor, 'disgust' and 'wellbeing' predicted overall liking of the ginger squash soup. These data suggest that: 1) PROP status and sensation seeking influenced responses to chili pepper but not ginger flavored soups and 2) different emotions predicted overall liking of the soups, though 'disgust' was a negative predictor for both. Further exploration into the role of emotions on preferences for pungent spices is warranted.